EXPLORATION STUDY USING PLASTIC WASTE IN CRAFT WORK IN CLASS X SMA NEGERI 1 BATURETNO - Nurpradana, Marafendi (Eduarts: Jurnal Pendidikan Seni, 2016)
Waste plastic is damp rubbish which is difficult to be separated and reduced, in order to decrease the amount of plastic rubbish needs a real action. The purpose of the research is to observe the process of waste plastic also the ability of the student of X IPA 4 SMA Negeri 1 Baturetno in crafting. The step of this research such as preface study and school survey, restrained observation, first meeting, restrained observation and second meetig. This research uses Scientific approach when doing the research in learning activities of crafting. The accumulation of the studentsâ€™ ability of crafting show 91,2% (31 student) get score 3,21-4 (best category) and 8,8% (3 student) get score 2,41-3,32 (good category). While the learning process, the students look enthusiastic to follow the learning activities. In the crafting process, students look enthusiastic when prepare tools, materials and collect the result on time. As result of the three dimension crafting are suitable with the previous design. The advice from researchers areÂ  teachers should choose the more appropriate learning media and be prepared before learning. Moreover, the teacher should develop the increase of ability of the student in analyzing visual object which is used to make craft in order to make the student more curious and communicative.Â